2014
DOI: 10.1525/as.2014.54.3.540
|View full text |Cite
|
Sign up to set email alerts
|

Local Levels of Participation in Japan's Foreign Aid and Cooperation

Abstract: A BSTRACTThis study will examine the determinants of local Japanese government involvement in decentralized international cooperation by taking an actor-specific approach to three outstanding cases: Shiga Prefecture, Kitakyushu City, and Yokohama City. It will look beneath the aggregate relationships to more qualitative evidence of localized motives for Japanese cooperation with developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Past literature revealed that socioeconomic factors, such as exports, foreign residents, and fiscal capacity, are not necessarily major causes to involvement with international Environmental Management and Sustainable Development ISSN 2164-7682 2020 collaboration activities, but there are materialistic motivations to get involved, such as the incentive to environmental-related businesses, and idealistic motivations, such as the environmental protection as a globally shared responsibility (Nakamura et al, 2010). Pioneering, policy learning and innovation, and political leadership were also considered important drivers for successful engagement in international cooperation (Takao, 2014). One example that has merged all of these motivations is Kitakyushu.…”
Section: International Cooperation Has Long Been An Important Instrument To Build Up the Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…Past literature revealed that socioeconomic factors, such as exports, foreign residents, and fiscal capacity, are not necessarily major causes to involvement with international Environmental Management and Sustainable Development ISSN 2164-7682 2020 collaboration activities, but there are materialistic motivations to get involved, such as the incentive to environmental-related businesses, and idealistic motivations, such as the environmental protection as a globally shared responsibility (Nakamura et al, 2010). Pioneering, policy learning and innovation, and political leadership were also considered important drivers for successful engagement in international cooperation (Takao, 2014). One example that has merged all of these motivations is Kitakyushu.…”
Section: International Cooperation Has Long Been An Important Instrument To Build Up the Relationshipsmentioning
confidence: 99%
“…The city was created in 1963, on Kyushu island, by the sea, in a favorable geographical position to exchange with foreign countries. During the first half of the 20th century, Kitakyushu"s steel manufacturing was the main contributor to Japanese economic development and, in the 1960s, it was one of the four largest industrial zones in Japan (Takao, 2014). The city became heavily polluted and, before the general public was aware of all environmental and health damage, the air pollution colors were called "rainbow of smoke", a symbol of progress and economic development (Akagi et al, 2018).…”
Section: International Cooperation Has Long Been An Important Instrument To Build Up the Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly the case in Japan that partially dispenses policies for export through local governments and private firms (Menju, 1999). While widespread in other regions, such an approach is specially embraced with as "decentralized international cooperation" and "public-private interest coordination" where both local SMEs and local governments, rather than state agents, are deployed to deliver aid to developing countries (Takao, 2014). Outside this development cooperation paradigm, public enterprises have also been involved in the development of cooperation between city governments concerned with technology and knowledge exchange.…”
Section: Introductionmentioning
confidence: 99%